The Effects of Students’ Perception of the School Environment and Students’ Enjoyment in Reading towards Reading Achievement of 4th Grades Students in Hong Kong - Astrid Karina Wingard; Hardika Dwi Hermawan; Vita Rosiana Dewi (Indonesian Journal on Learning and Advanced Education (IJOLAE), 2020)
The purpose of this study is to investigate some perceived factors in students reading achievement. This study focuses on the correlation between fourth graders’ safety feeling inside school environment and their reading enjoyment towards their reading achievement. Descriptive analysis used in this study and data draws from Progress in International Reading Literacy Study (PIRLS) 2016. The participants were 3349 students in their fourth year of schooling in Hong Kong where 49.1% were girls and 50.9% were boys. The range of the age was 8 to 15 years old. The result showed the importance of creating a safe school environment. Besides students’ perception of their school environment, students’ reading enjoyment was another factor which influenced reading achievement. Students’ perception of the school environment and students’ enjoyment in reading also affected students’ reading achievement, but the perception of reading is boring gave stronger effect to the reading achievement.